PERANCANGAN BUKU ILUSTRASI BATIK TUBAN SEBAGAI UPAYA PELESTARIAN NILAI-NILAI BUDAYA - Nugroho, Christ Sindhu Adi (Jurnal Art Nouveau, 2014)
Abstract: The emergence of the phenomenon of shifting cultural values contained in the motif by economic function raises concerns about the preservation of classic Indonesian batik motifs, especially the classic motifs of Tuban. Therefore, it takes a media design information in the form of book illustration to raise cultural values such as meaning, philosophy and myths contained in the classical batik Tuban. This design is done with the approach of observation, interviews and existing studies using the keyword viewpoint literature review results, namely the aesthetic, social, cultural, self-image and cultural products. By using descriptive-qualitative method of analysis that is supported by indicators STP and USP (Unique Selling Proposition) obtained